The Role of miR-155 gene expression in Rheumatoid arthritis: miR-155 Gene Effect in Rheumatoid Arthritis - Ghuraibawi, Fatimah; Muhammed, Haidar J.; Nabaa Ihsan Awadh (Iraqi Journal of Cancer and Medical Genetics, 2023)
Rheumatoid arthritis (RA) is a systemic autoimmune disease that is prolonged, inflamed, and causes progressive disability, MicroRNAs appear to influence autoimmune disease processes through systemic consequences , including the immune system's irritant activities,  in which specific antibodies with a high sensitivity for RA are the anti-CCP antibodies, Therefore, this research aims to evaluate the range of expression profile of circulating miRNA155 gene as a potential diagnostic biomarker in RA patients. The overall number comprised 36 RA patients, in addition to 14 healthy individuals as a comparison detection with ages ranging 20 to 60 years. All samples of patients and control suspected for diagnosed with anti-citrullinated protein antibodies test (ACPA) by immune assay for enzyme sorbent technique (ELISA). Relative quantification (RQ) of miRNA155 expression was performed after miRNA extraction from the serum of all study participants, was estimated using RT- qPCR. Significant Results noticed increased in expression of miRNA155 profile depending on the fold of expression (11.12 Fold expression  ± 1.08), in comparison to a healthy people so as  high significant (p ≤ 0.0001) of Anti-ccp Abs in patients with RA in  which at risk and assessed the change in expression levels.  In conclusion the study identified upregulation in circulated miRNA155 which may probably serve as prognostic form as biomarkers for disease in development.